The effect of protic solvents on the excited state proton transfer of 3-hydroxyflavone: A TD-DFT static and molecular dynamics study - Salaeh, Rusrina; Prommin, Chanatkran; Chansen, Warinthon; Kerdpol, Khanittha; Daengngern, Rathawat; Kungwan, Nawee (My University, 2018)
The effect of intermolecular hydrogen bonding played by protic solvents (ammonia, methanol and water) on the excited state proton transfer (ESPT) reaction of 3-hydroxyflavone (3HF) was theoretically investigated using density functional theory (DFT) and time-dependent DFT (TD-DFT). The formation of intermolecular hydrogen bond induced by protic solvents indicates that the intramolecular hydrogen bond may be interrupted in favor of a complex causing low quantum yield of keto emission and exhibiting dual emission (both enol and keto) in experiment. The strengthening of intermolecular hydrogen bond in the S1 state has been confirmed by the red-shift of IR vibrational spectra and shorter bond distances involving proton transfer (PT) process in comparison with those of the S0 state. From potential energy curves (PECs) of PT coordinate, PT process is likely to proceed in S1 state and PT in 3HF(NH3) occurs more easily than those of 3HF(CH3OH) and 3HF(H2O) due to its lower barrier. Moreover, on-the-fly dynamics simulations of all complexes were carried out to provide the detailed information on the PT mechanism. The dynamic results show that ESPT process of 3HF with protic solvent takes place through intermolecular hydrogen bond with slower PT time (259, 117 and 104 fs for 3HF(NH3), 3HF(CH3OH) and 3HF(H2O), respectively) than that of 3HF (76 fs) via intramolecular hydrogen bond. Furthermore, the ultrafast PT time is found to be nicely correlated with polarity of solvent and PT probability is also anti-correlated with PT barrier.
Keywords: 3-Hydroxyflavone; B3LYP; Excited state proton transfer (ESPT); Solvent effect; TD-DFT